Comparative study of internal communication management in public universities with high quality accreditation in Antioquia - Aristizábal Giraldo, María Eugenia; Hernández García, David (Folios, revista de la Facultad de Comunicaciones y Filología, 2016)
This article presents the results of a comparative study of internal communications management approaches in two public universities with high-quality accreditation in Antioquia (Colombia) as a basis for building a communications model for public institutions of higher education. For the analysis at each university (Universidad Nacional de Colombia and Universidad de Antioquia), interviews and focus groups with academic and administrative managers and communications professionals were held. Previous studies on university communications systems and communications theories were considered. Existing literature on organizational communication, quality management standards, and CNA guidelines, were key in the choice of the variables chosen for comparison. The analysis showed that the two universities share similar realities, such as a fragile articulation between the central communications system and communication flows in the academic units, a greater interest in media production than in formulating long-term strategies, and a lack of explicit policies for communications management, among others.